Gaps Between Self-Rated Job Importance and Abilities for Community Health Workers in Massachusetts. (July 2016) - Rataj, Suzanne; Weber, Luise; DiFulvio, Gloria; Heffernan, Dawn; Gerber, Dan; Chipkin, Stuart R.
Introduction: Community health workers (CHWs) serve increasingly active roles in clinical care and population health. To identify priorities for training programs, we developed a training needs assessment (TNA) tool by integrating and distilling core competencies previously identified by various national and state agencies. Methods: CHWs were asked to self-rate, using a 4-point scale, the importance to their work and their ability to perform 49 competencies categorized under 10 domains. A difference score—Ability minus Importance—was calculated to determine relative Need. Results: The 96 CHWs who completed the TNA were mostly female (80%) and Latino (40%). While CHWs indicated training was needed for all competencies, the scores ranged from −0.04 to −0.45, on a scale running from 0 to −3, where larger negative numbers indicate higher need. In general, there was a high level of congruence between individual competencies with high Need and domains with Need, with few outliers. Competencies with high Need scores related to culture, case assessment and coordination, and behavior change. CHWs rated client-based competencies higher than population health competencies in Ability scores (3.43 vs. 3.05, respectively) and Importance scores (3.70 vs. 3.35, respectively). However, overall Need scores showed no difference between client-based and public health-based competencies. Conclusion: CHWs can successfully rate the importance of core competencies to their work and rank their ability to perform these competencies. Training needs generally favored clinical individual client-focused skills over prevention and public health competencies. Using scales that incorporate self-rated measures of core competency ability and importance can inform priorities for CHW training programs and contribute to successful curriculum development.